1984
DOI: 10.1111/j.1365-2125.1984.tb02417.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of two strategies for improving patient recall of prior drug therapy.

Abstract: The ability to recall details of current and prior drug therapy was evaluated in two studies employing a total of 94 patients with inflammatory polyarthritis. Ten per cent of patients were unable to completely recall the names of their current anti‐inflammatory drugs and eighty‐three per cent of patients to completely recall the details of prior anti‐inflammatory drug therapy. Prompting firstly with the proprietary names of drugs and thereafter with a pill board substantially enhanced recall particularly for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Therefore, further research into their use may be warranted but future surveys should consider incorporating similar visual cues and a number of DHS surveys have already incorporated their use. Pill boards have been shown to improve accurate recall of drugs in other settings [22].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further research into their use may be warranted but future surveys should consider incorporating similar visual cues and a number of DHS surveys have already incorporated their use. Pill boards have been shown to improve accurate recall of drugs in other settings [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, research has shown that patients are often unable to tell exactly which medications they have been taking [2][3][4]. Even when they are requested to bring all their medication, there is no guarantee of completeness [5].…”
Section: Introductionmentioning
confidence: 96%
“…Mean HAQ score was 1.3 (95% CI 1.1-1.5). Mean aBMD was 0.991 (95% CI 0.956-1.026) g/cm 2 at the lumbar spine and 0.823 (95% CI 0.769-0.877) at the hip. Mean Z-scores were À0.314 (95% CI À0.631 to 0.003) at the lumbar spine and À0.509 (95% CI À0.922 to À0.095) at the hip.…”
mentioning
confidence: 99%
“…Dual energy X-ray absorptiometry of the lumbar spine and femoral neck was performed. Results were recorded as areal bone mineral density (aBMD, g/cm 2 ) and Z-scores. The associations between putative risk factors and BMD were examined using linear regression with adjustments for age, sex, height and weight.…”
mentioning
confidence: 99%